1992
DOI: 10.1523/jneurosci.12-09-03676.1992
|View full text |Cite
|
Sign up to set email alerts
|

Primary demyelination induced by exposure to tellurium alters Schwann cell gene expression: a model for intracellular targeting of NGF receptor

Abstract: Exposure of developing rats to tellurium results in a highly synchronous segmental demyelination of peripheral nerves with sparing of axons; this demyelination is followed closely by a period of rapid remyelination. Demyelination occurs subsequent to a tellurium-induced block in the synthesis of cholesterol, the major myelin lipid. We utilized the techniques of Northern blotting, in situ hybridization, and immunocytochemistry to examine temporal alterations in Schwann cell gene expression related to demyelinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…In control nerve, label was present in the perinuclear region of Schwann cells, as reported previously (Griffiths et al, 1989;Mitchell et al, 1990). Tellurium-treated nerves, as expected (Toews et al, 1992), showed a less intense perinuclear signal involving fewer cells (partial to complete down-regulation of myelin gene expression in all myelinating Schwann cells).…”
Section: Localization Of Mcp-1 Mrna Expression By In Situ Hybridizationsupporting
confidence: 86%
“…In control nerve, label was present in the perinuclear region of Schwann cells, as reported previously (Griffiths et al, 1989;Mitchell et al, 1990). Tellurium-treated nerves, as expected (Toews et al, 1992), showed a less intense perinuclear signal involving fewer cells (partial to complete down-regulation of myelin gene expression in all myelinating Schwann cells).…”
Section: Localization Of Mcp-1 Mrna Expression By In Situ Hybridizationsupporting
confidence: 86%
“…These findings are interesting in light of previous work that has shown that tellurium, an inhibitor of cholesterol biosynthesis at the squalene epoxidase step, causes reversible peripheral nerve demyelination in young rats, accompanied by downregulation of my- elin proteins, upregulation of p75, and SC proliferation, as SC revert to a precursor phenotype (WagnerRecio et al, 1991;Toews et al, 1992). The rather selective toxicity to peripheral nerve has been attributed to the relative demands for cholesterol synthesis, with myelin synthesis proceeding rapidly in the peripheral nerves of weanling rats.…”
Section: Caveolin-1 and Cholesterolmentioning
confidence: 60%
“…Serum GFAP levels are also increased in AIDP and CIDP. Experimental studies have shown that focal demyelination induces active proliferation of adjacent SCs, with reversion to a precursor cell phenotype expressing GFAP 8, 26. This may explain why GFAP is increased also in segmental demyelinating polyneuropathies such as AIDP and CIDP, although to a lesser extent than in a diffuse primary axonal degeneration.…”
Section: Discussionmentioning
confidence: 99%